Enhancing Seismic Capacity of Pile-Supported Wharves Using Yielding Dampers. (26th June 2013) - Mousavi, Seyed Amin; Bargi, Khosrow
Abstract : This paper presents a numerical study on the seismic response of pile-supported wharves equipped with metallic yielding dampers. Using 20 ground acceleration records, the contribution of the yielding damper is examined, and its main parameters are optimized through a parametric study. In the current study, considering coupling effects of different parameters, a new optimization procedure is proposed. The obtained results indicate that the stability condition of the retaining wall (quay wall) behind the wharf, period of the soil-wharf system, and also maximum allowable ductility ratio of the damper are the key factors affecting the optimum damper parameters. A simplified design guideline is proposed for either the design or the retrofit purposes followed by a numerical assessment to evaluate the contribution of the proposed damper on the seismic behavior of a typical pile-supported wharf. The obtained results show that yielding dampers, through their nonlinear behavior, can dissipate a large portion of seismic input energy and mitigate piles damages which have been observed in earlier earthquake events.